Contribución de la reparación colectiva a la construcción de paz territorial: caso comunidad del Alto Simacota, Santander, Colombia (2020)
This article is a case study of the community of Alto Simacota (Santander, Colombia), which was the subject of the implementation of an administrative program of collective reparation. It makes a theoretical review of collective reparation, surveys this administrative process during its years of implementation in the community in question, presents a description of the concept of territorial peace held by this community, and, lastly, analyzes the contributions provided by the administrative process of collective reparation to the construction of territorial peace for this community. This text gives an account of the achievements to date in terms of community rehabilitation and satisfaction measures, while highlighting the low impact of restitution actions and guarantees of non-repetition, reaching the conclusion that there is still a debt on the part of State institutions in fulfilling the right to comprehensive reparation and in contributing to peace-building.